The Food System Summit’s Failure to Address Corporate Power - Clapp, Jennifer; Noyes, Indra; Grant, Zachary (Development, 2021)
Based on analysis of documentation associated with the UN Food Systems Summit process, we identify three main ways in which the Summit failed to address the problem of corporate power in food systems in a meaningful way. First, the Summit was ‘strategically silent’ on the problem of corporate power, mentioning the problem only very infrequently and in a way that failed to identify corporations as holding disproportionate power in food systems. Second, it advanced technology and innovation-based solutions that benefit large agrifood companies rather than seeking structural transformation of food systems. Third, it gave corporations a priority seat at the table by engaging them in various settings in the lead up to the Summit.